2009
DOI: 10.1158/1541-7786.mcr-08-0021
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Fibroblast Growth Factor Receptor-2 Mutations in Melanoma

Abstract: We report that 10% of melanoma tumors and cell lines harbor mutations in the fibroblast growth factor receptor 2 (FGFR2) gene. These novel mutations include three truncating mutations and 20 missense mutations occurring at evolutionary conserved residues in FGFR2 as well as among all four FGFRs. The mutation spectrum is characteristic of those induced by UV radiation. Mapping of these mutations onto the known crystal structures of FGFR2 followed by in vitro and in vivo studies show that these mutations result … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 39 publications
4
84
1
2
Order By: Relevance
“…2C , extracellular domain; ref. 31 ) in cis with the V472M "gatekeeper" mutation that induces resistance to FGFR inhibition ( 6 ). As expected, ectopic expression of the V472M gatekeeper mutation alone resulted in resistance to FGFR inhibition in H1581 cells ( Fig.…”
Section: Control Virussupporting
confidence: 64%
See 1 more Smart Citation
“…2C , extracellular domain; ref. 31 ) in cis with the V472M "gatekeeper" mutation that induces resistance to FGFR inhibition ( 6 ). As expected, ectopic expression of the V472M gatekeeper mutation alone resulted in resistance to FGFR inhibition in H1581 cells ( Fig.…”
Section: Control Virussupporting
confidence: 64%
“…2C and D ), which is analogous to the R251Q mutation of FGFR2. This mutation strongly interferes with ligand binding to FGFR2 ( 31 ). We further predicted fi ve other extracellular mutation sites in the Inter-IgG2-IgG3 domain (ref.…”
Section: Control Virusmentioning
confidence: 93%
“…FGFR1 overexpression (14) and activating FGFR1 gene mutation (49) have been also reported in melanoma. Finally, approximately 10% of melanoma tumors and melanoma cell lines harbor inactivating, loss-of-function mutations in the FGFR2 gene (50). The ability to interact with different FGFs without interacting with FGFRs makes PTX3 a multitarget "FGF ligand trap" for those lesions characterized by an aberrant production of one or multiple FGF family members.…”
Section: Discussionmentioning
confidence: 99%
“…To control for nonspecific binding, the FGFR2c R251Q mutant was coupled to the control flow channel of the chip. The R251Q mutation maps to the linker region between D2 and D3 of FGFR2c, and we have previously shown that this mutation results in a major loss of ligand binding because it eliminates key hydrogen bonds between FGFR and FGF (64). To examine binding of mutated FGFR2b ligand-binding regions to FGF1, full-length FGF1 was immobilized on a chip, and FGFR2b…”
Section: Methodsmentioning
confidence: 99%